2022
DOI: 10.3390/app12020831
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Polyphenols from Olive Leaves Employing Deep Eutectic Solvents: The Application of Chemometrics to a Quantitative Study on Antioxidant Compounds

Abstract: The extraction of phenolic compounds from olive leaves was optimized using three glycerol-based deep eutectic solvents (DESs) with lysine, proline, and arginine. A three-level Box–Behnken design was used to examine the influence of the liquid/solid ratio, concentration of DESs, and extraction temperature on the yield of the extraction process. A second-order polynomial model was used for predicting the polyphenol extraction yield. The optimal predicted conditions were used for extractions and they provided the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 78 publications
(85 reference statements)
0
10
0
Order By: Relevance
“…In this work, the oleuropein level in Oblica was higher than in other cultivars, especially the oleuropein isomer c (10.217 mg/g). Previous studies showed that the concentrations of oleuropein in olive leaves vary considerably due to the type of cultivar, climatic and geographical conditions, sampling and drying techniques of the plant material, and the extraction parameters [ 7 , 13 , 17 , 41 , 42 ]. Irakli et al [ 43 ] investigated the influence of UAE conditions (solvent type and concentration, extraction temperature, and time) on the extract yield of oleuropein and flavonoids from olive leaves and concluded that its yield increased significantly when the concentration of all solvents increased up to 50%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the oleuropein level in Oblica was higher than in other cultivars, especially the oleuropein isomer c (10.217 mg/g). Previous studies showed that the concentrations of oleuropein in olive leaves vary considerably due to the type of cultivar, climatic and geographical conditions, sampling and drying techniques of the plant material, and the extraction parameters [ 7 , 13 , 17 , 41 , 42 ]. Irakli et al [ 43 ] investigated the influence of UAE conditions (solvent type and concentration, extraction temperature, and time) on the extract yield of oleuropein and flavonoids from olive leaves and concluded that its yield increased significantly when the concentration of all solvents increased up to 50%.…”
Section: Resultsmentioning
confidence: 99%
“…The phenolic profile of olive leaves varies within cultivar and is influenced by the timing of sampling/harvest, climatic conditions, geographical origin, age and biological cycle of the tree, agricultural practices applied, and conditions during extraction/isolation, processing, storage, etc. [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The diffusivity of tyrosol from olive leaf tissues is partially reliant on certain conditions of the extraction system. A recent report by Akli et al, 39 proposed an optimized extraction protocol using deep eutectic solvents mixed with different amino acids including lysine which represented 53 420.23 mg per g tyrosol in the extracts, that was signicantly higher than that obtained by using a conventional solvent with 70% ethanol (19 398.64 mg g −1 ). These authors observed that the content of tyrosol was greater than that of hydroxytyrosol and oleuropein (this is typically different from what can be expected) and explained that the probable reasons can be the high stability of tyrosol and solvent suitability for tyrosol recovery.…”
Section: Recovery Of Principal Polar Phenols From Olive Leaveschromat...mentioning
confidence: 94%
“…Polyphenols also occur in the leaves [ 287 ]. These compounds confer bioactive properties on olive leaf extracts, such as antioxidant, antimicrobial, and antitumor activity; the capacity to reduce the risk of coronary heart disease was also reported [ 288 ].…”
Section: Phytochemicals From Crop Residuesmentioning
confidence: 99%